Análise do efeito da diversidade sociocultural na interação homem-robô por meio de gestos - Brito, Ícaro de Vasconcelos (2019)
This work presents a between-subjects elicitation study that aims to analyze the effect of sociocultural diversity on gesture-based human-robot interaction. In this study, participants are sorted in pairs of groups according to the factors gender, technological insertion level and culture. Then, they are invited to perform gestures to control a mobile robot from eight given tasks. The proposed movements are video recorded and classified by the researchers, who statistically analyze the level of agreement between the pairs of groups. In addition, for each task transmitted to the robot, the participants assess the goodness and the easiness of the gesture proposed, as well as indicate which interaction mode would be the most appropriate for that scenario. The results show that sociocultural factors do not influence the type of gesture used and, in most cases, do not have a significant effect on the choice of gestures for interaction. The most common types of gesture movements were dynamic, iconic, and with one or two hands, but users also used mimic and full-body gestures for more abstract tasks. Overall, the performed gestures were well evaluated by the participants in the goodness and easiness aspects, especially dynamic, iconic and one-hand gestures. In addition, using gestures was a well-accepted interaction mode by different sociocultural groups for most tasks. However, the study highlights that, regardless the sociocultural profile, the user is less positive to gestures and less consistent in the proposals when commands are required for abstract functions. In these cases, the participants prefer to use the voice as the interaction mode.